Denial-of-Service attacks on 6LoWPAN-RPL networks: Issues and practical solutions - RGHIOUI, Anass; KHANNOUS, Anass; BOUHORMA, Mohammed (Journal of Advanced Computer Science & Technology, 2014)
RPL (Routing Protocol for Low-power and lossy networks) is a specific routing protocol designed to optimize 6LoWPAN (IPv6 over Low power Wireless Personal Area Network) operation. As 6LoWPAN suffers from resource constraints on battery, processor, memory and bandwidth, it affects the performance of the RPL protocol. From security point of view, this will make RPL vulnerable to several threats directly or indirectly. Thus, cryptographic systems are not sufficient to protect the RPL from internal attacks; a compromised node from the network may cause undesired operation without being detected by these systems. An intrusion detection system (IDS) should be used, but it is not easy given the nature of 6LoWPAN; on a side its resource constraints, and on the other side its opening to the outside world through the Internet. In this paper we focus on denial of service (DoS) attacks, we determine the elements to be taken into account in selecting a compatible IDS and we give some solutions that we consider effective and valid for 6LoWPAN-RPL based networks Keywords: RPL, ROLL, 6LoWPAN, IDS, DoS, Network security.